2012
DOI: 10.1002/ange.201205943
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrogen/Deuterium Exchange of Unactivated Carbon–Hydrogen Bonds by a Pentanuclear Electron‐Deficient Nickel Hydride Cluster

Abstract: Austauschbar: Der Cluster [(iPr3P)Ni]5H6 (1; siehe Bild) wurde durch Zugabe von Wasserstoff zu dem zweikernigen Stickstoff‐Komplex [(iPr3P)2Ni]2(μ‐N2) erhalten. Dieser beispiellose Cluster der ersten Übergangsmetallreihe hat ein Elektronendefizit und ist hochreaktiv. Komplex 1 tauscht in deuteriertem Benzol bei Raumtemperatur mit einer Halbwertszeit von 27 Minuten Wasserstoffatome gegen Deuterium aus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The room-temperature addition of 1 to deuterated arenes, such as C 6 D 6 and C 7 D 8 , provides the isotopologues 1- d n (where n = 1–6), as shown in Scheme , along with isotopologues of the arene. These reactions proceed at room temperature, and the degree of H/D exchange into 1 is easily monitored by 31 P­{ 1 H} NMR, because the resonances for 1- d 0–6 have large temperature-dependent isotope shifts that arise due to a low-energy paramagnetic state . The extent of the isotope shift is dependent upon the degree of deuteration, with a separation between the 1- d 0 and 1- d 1 31 P­{ 1 H} NMR shifts of 0.9 ppm, and a separation between the 1- d 5 and 1- d 6 shifts of 0.6 ppm, at 298 K. The incorporation of deuterium into 1 gives a statistical mixture of 1- d 0–6 that can be modeled to accurately determine the percent deuteration, and thus monitor the rate of H/D exchange.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The room-temperature addition of 1 to deuterated arenes, such as C 6 D 6 and C 7 D 8 , provides the isotopologues 1- d n (where n = 1–6), as shown in Scheme , along with isotopologues of the arene. These reactions proceed at room temperature, and the degree of H/D exchange into 1 is easily monitored by 31 P­{ 1 H} NMR, because the resonances for 1- d 0–6 have large temperature-dependent isotope shifts that arise due to a low-energy paramagnetic state . The extent of the isotope shift is dependent upon the degree of deuteration, with a separation between the 1- d 0 and 1- d 1 31 P­{ 1 H} NMR shifts of 0.9 ppm, and a separation between the 1- d 5 and 1- d 6 shifts of 0.6 ppm, at 298 K. The incorporation of deuterium into 1 gives a statistical mixture of 1- d 0–6 that can be modeled to accurately determine the percent deuteration, and thus monitor the rate of H/D exchange.…”
Section: Resultsmentioning
confidence: 99%
“…The past decade has seen several reports of transition metal clusters , undergoing unprecedented bond transformations with traditionally inert bonds, including the activation of C–C bonds in hydrocarbons such as benzene , and ethylene . This has spurred on the rational design of transition metal clusters and polynuclear complexes, in an attempt to access similar cooperative reactivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzene-d 6 was dried by heating at reflux with Na/K alloy in a sealed vessel under partial pressure and then trap-to-trap distilled and freeze−pump−thaw degassed three times. Cluster 1 21 and [( i Pr 3 P)Ni] 2 N 2 75 were synthesized as per literature procedures. N-Methylmorpholine oxide, benzonitrile, and lithium borohydride were purchased from Sigma-Aldrich, and their purity was confirmed through NMR spectroscopy.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The electron-deficient Ni hydride cluster [( i Pr 3 P)Ni] 5 H 6 (1) has been shown to perform catalytic H/D exchange with arenes 21 and ultradeep hydrodesulfurization, 22 as shown in Scheme 1. Recently, it was shown that 1 can abstract a carbon from alkenes by C−H activation and carbon−carbon bond cleavage.…”
Section: ■ Introductionmentioning
confidence: 99%